Pregnant Women with Probable Psychological Issues at Al-Furat Al-Awsat Teaching Hospital in Al-Najaf Province - Kareem, Russell Abbas; Ibadi, Atheer Kadhim (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Pregnancy is a critical period characterized by high psychological vulnerability, with potentially negative consequences on the health of the mother and her child. Therefore, the assessment of pregnant women is important in all dimensions. There is limited research on prenatal psychological issues in Iraq. Objectives:To assess the prevalence of the most common psychological problems, including depression, anxiety, and stress for pregnant women during pregnancy. Design and sample:This pilot study was a cross-sectional study design. A simple random sampling of 91 pregnant women at Al-Furat Al-Awsat Teaching Hospital in Najaf, Iraq. Measurements: Standardized questionnaires as data collection tools, collecting information on socio-demographic characteristics, obstetric history, psychological and social history, and conducting assessments for anxiety, depression, and stress through interviews with pregnant women. Results:The findings of the study indicated that (81.3 %) have moderate perceived stress levels, (42.9%) have moderate pregnancy-related anxiety, and (38.5%) have severe pregnancy-related anxiety. Regarding prenatal depression, most pregnant women(80.2%) have high levels of depression and need to be referred to a psychiatric specialist for more investigation and early intervention. Conclusion: Stress, anxiety, and depression are common among pregnant women and often occur together. Therefore, assessing the psychological state of pregnant women is essential in reducing the resulting burden and preserving the health of the mother and her fetus.